A new mathematical method for quantifying trajectory of buoyant line-source gaseous fuel jet diffusion flames in cross air flows. (1st August 2016) - Zhang, Xiaochun; Xu, Wenhao; Hu, Longhua; Liu, Xiaozhou; Zhang, XiaoLei; Xu, Wenbin
Abstract: The gas leakage from a gaseous fuel pipeline usually leads to a jet fire, which causes both enormous loss of energy and thermal threat to the surrounding objects. The potential wild fire risk is a significant issue and need to be paid sufficient attention. This paper investigates the vertical flame height, horizontal flame length and provides a new mathematical method to quantify the trajectory of the flame produced by a linear buoyant turbulent jet fire, which can be resulted in due to pipeline fuel leakage, in cross air flows. Experiments are carried out by a 2 mm (width) ∗ 142.5 mm (length) line-source nozzle employing propane as fuel. The velocities of cross air flows are ranged from 0 m/s to 2.5 m/s. It is found that the vertical flame height and horizontal flame length can be well predicted by initial momentum ratio ( r ) and Froude number ( Fr ). A simple and easily applied explicit mathematical method is proposed to predict the trajectory length based on circumference approximation. All these findings can contribute to both combustion science and providing guidance for the wild jet fire risk assessment.